2021
DOI: 10.1016/j.sjbs.2021.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Chamomile flower extract ameliorates biochemical and histological kidney dysfunction associated with polycystic ovary syndrome

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In addition, similar studies have shown that Chamomile, with its phytoestrogens and antioxidant properties, reduces FSH levels of testosterone, oxidative stress, estradiol, and LH and improves ovarian histological changes in mice with PCOS by disappearing cysts and increasing the number of follicles [ 17 , 43 ]. As a result, based on the study’s findings, it seems that the single and combined use of these two extracts can improve ovarian function changes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, similar studies have shown that Chamomile, with its phytoestrogens and antioxidant properties, reduces FSH levels of testosterone, oxidative stress, estradiol, and LH and improves ovarian histological changes in mice with PCOS by disappearing cysts and increasing the number of follicles [ 17 , 43 ]. As a result, based on the study’s findings, it seems that the single and combined use of these two extracts can improve ovarian function changes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the extract showed a protective effect against formaldehyde in male rats' reproductive system [49] and against torsion/detorsion-induced damages on adult rat testis tissue [188] and ovary tissue [189]. On the other hand, M. chamomilla extracts showed a therapeutic effect against thyroid damage [190] and kidney dysfunction [191] associated with polycystic ovary syndrome in female rats.…”
Section: Phyotherapeutical Applicationsmentioning
confidence: 95%
“…Serum concentrations of urea and BUN may increase with Met therapy. (58) Ocimum kilimandscharicum, letrozole and metformin…”
Section: Metformin and Gnrh Agonistsmentioning
confidence: 99%